Tácito, ¿inspirador de la carrera política del Conde-Duque de Olivares? (Minerva, 2019)
The studies about the figure of the Count-Duke of Olivares and our knowledge of Tacitism in Spain in the 17th Century coincide on the fact that Tacitus had a great influence on the favourite of King Philip IV. From this angle and not intending to explain Olivares political programme only in the light of Tacitus, we would like to point out several coincidences (coincidences?) that we noticed between the favourite's court career and the work of the Latin historian or the precepts that the writers of historic political treaties in the 17th Century took from this classical historian.